La Nouvelle Chanson Chilienne : contre l’oubli de l’Histoire et des histoires - Aurélie Prom (Les Cahiers de Framespa)
Musical movement politically engaged that appeared in the 1960’s and followed the line of work in research and creation of the Research Institute o Musical Folklore of the Universidad de Chile, the Nueva Canción Chilena became the voice of a silenced majority. Witnesses of their time, the authors and compositors Víctor Jara, Violeta Parra and even Luis Advis tell significant events and demand sociopolitical changes that socialism would be able to bring. Nevertheless, they also tried to fight against forgetting historical events that were too occasionally registered by the official history and however left their mark on popular imagination. This is how they also tried to restore truths that the elite preferred to ignore. Those troubadours revisited inglorious episodes of Chilean History that shouldn’t be forgotten, using personal stories to tell a greater story, to build a better future for the Chilean nation would be possible.